THE MOTION COMIC JAKA BEREK - -, Sutikno -; Supriyanto, Eko (ARTISTIC : International Journal of Creation and Innovation, 2020)
In the past, people watched a theater called Ludruk on the mobile stage and on television. However, currently Ludruk's art is almost out of date. From this phenomenon, the researchers formulated the problem, namely how the local story artworks of Sawonggaling content can be transformed into a motion comic animated film using a three-act structure. The method of making comic motion animation for the legend of Jaka Berek uses two approaches, namely the method of making animation and the method of making comics. Both of them are done in 3 stages, namely pre-production, production and post-production. The results of the making of this motion comic animation show that the effort to bring back the legendary story that has long been drowned requires some appropriate medias that is easily understood by the current generation. The making of motion comics originating from legendary stories must be based on research and literature studies in order to give the spirit to the artwork that will be produced.